Comparison of the chemical and natural control of Asian citrus psyllid Diaphorina citri - Reyes-Rosas, Marco A.; Loera-Gallardo Jesús; López-Arroyo José I. (Revista Mexicana de Ciencias Agrícolas, 2018)
The effectiveness of the insecticide omethoate (Folimat ® 1000) and of the native natural enemies of the Asian citrus psyllid to control this pest was compared in Río Bravo, Tamaulipas, in 2010. The results indicated that omethoate was more effective, as no nymphs or adults were observed 264 h after its application; on the other hand, after 72 h of the treatment with natural enemies, the nymphal population was reduced to levels similar to those achieved with the omethoate treatment. With the absolute control, the nymphal population increased over 100% after 264 h.